Why Huawei Isn't So Scary. - Kania, Elsa B.; Sheppard, Lindsey R. (Foreign Policy)
The article focuses on the issues regarding 5G telecommunication in front of Huawei. It mentions Huawei has amassed a market share estimated at nearly 30 percent of the global telecom equipment industry reflects its capacity to underbid and undercut competitors not to mention multiple alleged incidents of bribery and corruption. It presents views of Ren Zhengfei, chief executive officer (CEO) at Huawei, on the limiting Huawei's access to U.S. technologies.